Kajian Morfologis Kopus Digital Terhadap Medsos di Aplikasi Youtube pada Channel Arifah Rianti - Fina Damayanti; Andi Ruhul Wahyuni; Nensilianti; Johar Amir (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study analyses the morphosyntactic aspects of podcasts on Arifah Rianti's YouTube channel, with a primary focus on word segmentation and the use of non-standard language in social media communication. The research method applied was qualitative, with digital corpus analysis in the form of video transcripts of a podcast entitled ‘Podcast Penuh Emosi!! Duo Bahlul di Bikin Naik Darah sama Halda & Arafah!!’ The results of the study show various forms of word truncation that reflect the characteristics of casual and expressive spoken language, as well as the adaptation of Indonesian in the digital context. These findings confirm the dynamic development of slang on social media, which significantly influences morphosyntactic structure. This research makes an important contribution to understanding the transformation of Indonesian in the digital era and serves as a reference for the development of contextual language learning.